Serum Vitamin D Status in Older Adults: A Cohort Study - Simin Mouodi; Sajedeh Delbari; Seyed Reza Hosseini; Reza Ghadimi; Ali Bijani (Iranian Journal of Medical Sciences, 2023)
Background: Vitamin D is best known as a key regulator of bone metabolism and calcium and phosphate homeostasis. This study aimed to assess the effect of different factors on the five-year changes in serum vitamin D concentration among older adults.Methods: This cohort study was conducted on adults aged ≥60 years living in Amirkola, in the North of Iran, from 2012 to 2017. Serum 25-hydroxyvitamin D (25-OH vitamin D) concentrations of <20, 20-29.99, and ≥30 ng/mL, respectively, were used to designate vitamin D deficiency, insufficiency, and sufficiency. Any variation between the second and baseline values of the 25-OH vitamin D concentration was reported as a five-year difference. Data were analyzed using SPSS version 17.0, and Chi square, t test, one-way ANOVA, and Tukey HSD post hoc tests were employed. P values less than 0.05 were considered statistically significant.Results: The mean serum concentration of 25-OH vitamin D at baseline and follow-up examination in 1011 individuals was 34.68±33.18 and 23.88±14.91, respectively (P<0.001). Following a five-year follow-up, vitamin D deficiency, insufficiency, and sufficiency were found in 452 (44.7%), 334 (33.0%), and 225 (22.3%) cases, respectively. The reduction in serum 25-OH vitamin D concentration after five years was significantly influenced by the administration of vitamin D (P=0.013) and calcium (P=0.007) supplements, serum profile of parathyroid hormone (PTH) (P=0.010), calcium (P=0.021), and phosphorous (P=0.021). However, age, sex, body mass index, metabolic syndrome, and physical activity had no significant impact (P>0.05). Conclusion: Regardless of age, sex, body mass index, metabolic syndrome, or physical activity, the mean serum concentration of vitamin D decreased over a five-year follow-up.